Release of Pea Germplasm with Fusarium Resistance Combined with Desirable Yield and Anti‐Lodging Traits. Issue 2 (31st January 2014) - Porter, Lyndon D.; Kraft, John M.; Grünwald, Niklaus J.
Abstract : Six F13 pea ( Pisum sativum L.) breeding lines, 00‐5001 (Reg. No. GP‐108, PI 669372), 00‐5003 (Reg. No. GP‐109, PI 669373), 00‐5004 (Reg. No. GP‐110, PI 669374), 00‐5005 (Reg. No. GP‐111, PI 669375), 00‐5006 (Reg. No. GP‐112, PI 669376), and 00‐5007 (Reg. No. GP‐113, PI 669377), were developed by the USDA–ARS, Prosser, WA, via single‐seed descent. The lines were developed with traits augmenting yield and harvestability combined with partial resistance to Fusarium root rot caused by Fusarium solani (Mart.) Sacc. f. sp. pisi (van Hall) Snyd. and Hans ( Fsp ) and resistance to Fusarium wilt caused by Fusarium oxysporum Schlecht. f. sp. pisi ( Fop ) races 1, 2, and 5. The six lines selected all demonstrated partial resistance to Fsp and resistance to Fop races 1 and 5, while maintaining double or triple pods per node associated with high yields. Four lines also demonstrated resistance to Fop race 2 combined with semi‐leafless leaf types, which promote uniform seed color and anti‐lodging characteristics. The mean disease severity ratings for Fusarium in all field trials were 50 to 58% less than the susceptible cultivar Bolero. These lines also yielded significantly more than Bolero in field trials in 2008 to 2009. Greenhouse trials confirmed resistances to Fop races 2 and 5 of specific lines. These lines will serve the dry, canning, and freezer pea industries as parents to improve resistance to Fusarium pathogens, which negatively impact the pea industry worldwide.